2006
DOI: 10.1111/j.1095-8312.2006.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of colour in the reaction of passerine predators to aposematic prey: experiments with mutants of Pyrrhocoris apterus (Heteroptera)

Abstract: Persistent questions concerning the warning coloration of unpalatable insects address whether the bright aposematic colour itself or its combination with a species-specific dark pattern is the key factor in their protection against insectivorous birds, and how chromatic polymorphism originates and is maintained in aposematics. In the present study, these questions were tested experimentally, using the birds Parus major , Parus caeruleus , Erithacus rubecula , and Sylvia atricapilla as predators, and chromatica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 50 publications
3
77
1
Order By: Relevance
“…This leads to the conclusion that detectability might be a more important determinant of survival rate than acceptability, even for a larva whose appearance allows one to expect the opposite. In particular, aposematic larvae are not safe because bird species differ in their ability to discriminate between aposematic and nonaposematic prey (Exnerová et al, 2003), also the threshold signal strength that creates the aversion appears to vary (Exnerová et al, 2006). The birds' willingness to consume aposematic prey also strongly depends on their hunger level as the results of the current and some other studies show (Chai, 1986;Sandre & Mappes, in prep.).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This leads to the conclusion that detectability might be a more important determinant of survival rate than acceptability, even for a larva whose appearance allows one to expect the opposite. In particular, aposematic larvae are not safe because bird species differ in their ability to discriminate between aposematic and nonaposematic prey (Exnerová et al, 2003), also the threshold signal strength that creates the aversion appears to vary (Exnerová et al, 2006). The birds' willingness to consume aposematic prey also strongly depends on their hunger level as the results of the current and some other studies show (Chai, 1986;Sandre & Mappes, in prep.).…”
Section: Discussionmentioning
confidence: 60%
“…Quite obviously, detectability is higher if the body is larger, and, somewhat less obviously, there is some evidence that aposematic prey has a steeper size dependent detectability function, as compared to cryptic objects (Mänd et al, 2007;this study). This is biologically relevant because warning colouration rarely offers complete protection to the aposematic prey (Stimson & Berman, 1990;Geffeney et al, 2002;this study), and high detectability may thus be highly detrimental (Exnerová et al, 2003(Exnerová et al, , 2006Endler & Mappes, 2004). Such a trade-off situation may imply that warning colouration is the optimal solution for some intermediate body sizes, while most animals smaller and larger than that are selected to be cryptic, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Achromatic signals (black and white) (C) have great variation, indicating that these colors should not be considered a reliable warning signal. and orange stimuli (Exnerová et al, 2006b). However, these studies do not determine why these associations are made with such color types (i.e., the underlying mechanism for what makes such colors effective signals).…”
Section: Discussionmentioning
confidence: 99%
“…However, Aronsson and Gamberalle-Stille (2008) showed that the pattern of a warning signal may not be as important as the color component. Moreover, a completely black prey may not elicit an avoidance response from an avian predator (Exnerová et al, 2006b). Our analyses show that black signals are highly variable both during the day and between weather conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation